Clinical trial protocol for TRANSFORM‐UK: A therapeutic open‐label study of tocilizumab in the treatment of pulmonary arterial hypertension. (1st November 2017) - Hernández‐Sánchez, Jules; Harlow, Louise; Church, Colin; Gaine, Sean; Knightbridge, Emily; Bunclark, Kate; Gor, Dee; Bedding, Alun; Morrell, Nicholas; Corris, Paul; Toshner, Mark
Abstract : Our aim is to assess the safety and potential efficacy of a novel treatment paradigm in pulmonary arterial hypertension (PAH), immunomodulation by blocking interleukin‐6 (IL6) signaling with the IL6 receptor antagonist, tocilizumab. Inflammation and autoimmunity are established as important in PAH pathophysiology. One of the most robust observations across multiple cohorts in PAH has been an increase in IL6, both in the lung and systemically. Tocilizumab is an IL‐6 receptor antagonist established as safe and effective, primarily in rheumatoid arthritis, and has shown promise in scleroderma. In case reports where the underlying cause of PAH is an inflammatory process such as systemic lupus erythematosus, mixed connective tissue disease (MCTD), and Castleman's disease, there have been case reports of regression of PAH with tocilizumab. TRANSFORM‐UK is an open‐label study of intravenous (IV) tocilizumab in patients with group 1 PAH. The co‐primary outcome measures will be safety and the change in resting pulmonary vascular resistance (PVR). Clinically relevant secondary outcome measurements include 6‐minute walk distance, WHO functional class, quality of life score, and N‐terminal pro‐brain natriuretic peptide (NT‐proBNP). If the data support a potentially useful therapeutic effect with an acceptable risk profile, the study will be used to power a Phase III study to properly address efficacy.